Development of an ELISA Using a Native Salmonella typhi 50kDa Antigen for Detection of IgA Anti-typhoid Antibodies in Human Sera - Hung, Kiu Siik (2004)
Typhoid fever remains an unsolved public health problem especially in the Third World countries like Philippines, Vietnam and Indonesia. Hence, a study on the reliability of an enzyme-linked immunosorbent assay (ELISA) for the detection of typhoid fever was conducted. This ELISA test measures the concentration of IgA against Salmonella typhi in human serum. This test is an indirect ELISA, based on a method that makes use of a 50k.Da outer membrane protein specific for S. typhi as the solid-phase antigen. Peroxidase conjugated rabbit anti-human lgA and ortho-phenylenediamine as chromogen for the substrate were used to detect the presence of serum IgA bound to the solid-phase antigen. The amount ofigA was determined by reading the OD of the chromogen substrate using an ELISA reader at a wavelength of 492nm and 620nm as reference wavelength. The optimal antigen coating concentration of the 50kDa antigen was 20J.!g/ml, determined by checker-board titration. lgA anti-typhoid antibodies were expressed as arbitrary units (Au) based on an lgA positive acute typhoid fever subject which was designated as I 00 Au. The results of this study confirmed that the ELISA has a high reliability for the detection of typhoid fever in human sera, based on the finding of a high degree of diagnostic sensitivity (83.3%) and specificity (96%). The cut-off value, defined as the mean plus 2SD of normal human serum was 5.1 Au (n=50). Intra-assay CV was 4.8% (n =54) and inter-assay CV was 7.1% (n = 5). This assay offers advantages of speed, simplicity, and sensitivity over conventional cell-culture methods for detection of typhoid fever.